Perjanjian Perkawinan: Sebuah Analisis Terhadap Putusan Mahkamah Konstitusi 69/PUU-XIII/2015 - Hapsari, Hening (UI Scholars Hub, 2023)
Marriage agreements remain a frequently debated and somewhat sensitive issue within the context of matrimony in Indonesia, notwithstanding their explicit existence in the country's legal regulations. Governed by the Marriage Law Number 1 of 1974 and addressed in the Civil Code (KUHPerdata/BW), marriage agreements are formulated by spouses before the solemnization of the marriage. However, a significant development occurred in 2015 when a constitutional challenge was raised against Article 29 of the Marriage Law Number 1 of 1974. In its definitive decision, the Constitutional Court ruled that marriage agreements could be established before, during, or after the marriage ceremony. This has engendered a considerable amount of both support and opposition, considering the numerous shifts that have ensued, such as legal inconsistencies, the potential for legal circumvention, and adverse consequences for the involved parties. Key words: Marriage Agreement, Constitutional Court Decision, Analysis.